Time of day variation in door-to-balloon time for STEMI patients in Los Angeles County: Does time of day make a difference?. (September 2013) - Shavelle, David M.; Zheng, Ling; Ottochian, Marcus; Wagman, Brittany; Testa, Nicholas; Hall, Stephanie; Koenig, William; Chan, Linda S.; Matthews, Ray V.
Abstract: Objective: Evaluate treatment times and clinical outcome in a consecutive series of ST segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI) in Los Angeles County. Background: Primary PCI for STEMI is beneficial if performed in a timely manner. Conflicting data exist regarding potential treatment delays for primary PCI performed during off hours. Methods: The Emergency Medical Services STEMI Receiving Center Database was queried from 2007 to 2009 to identify patients with a pre-hospital ECG showing STEMI who underwent PCI. On-hour PCI (On-hour Group, n = 1324) was defined as PCI occurring from 8 am to 5 pm and off-hour PCI (Off-hour Group, n = 922) was defined as occurring from 5 pm to 8 am. Treatment times, length of stay, vascular complications, achievement of TIMI 3 flow and in-hospital mortality were evaluated. Results: Off-hours PCI occurred in 41% of patients. Medical contact to door time was similar in the Off-hour Group compared to the On-hour Group, 20.7 ± 14.6 versus 20.3 ± 12.3 min, respectively, P = 0.47. In patients with available data ( n = 1366), the door-to-catheterization laboratory (CL) activation time was significantly shorter in the On-hour Group as compared to the Off-hour Group, −4.9 ± 11.9 versus –0.2 ± 27.5 min, respectively, P < 0.0001. Door-to-balloon time was significantly longer in the Off-hour Group compared to the On-hour Group, 74 ± 35 versus 60 ± 26 min respectively, P < 0.0001. Length of stay, vascular complications, final TIMI 3 flow and in-hospital mortality were similar between both groups. Conclusions: In STEMI patients receiving primary PCI in Los Angeles County, off-hour PCI was common. Short-term clinical outcomes were similar despite longer door-to-balloon time in patients receiving off-hour PCI. The longer door-to-balloon time in the off-hour PCI patients were partly explained by longer door-to-CL activation time.